Negative electrode material and high-energy-density sodium ion battery

By using spherical hard carbon with surface-coated Na2Ti6O13 and specific positive electrode materials and electrolyte formulations in sodium ion batteries, the challenges of sodium ion batteries in energy density and circulation performance are solved, and the combination of high energy density and good circulation performance is achieved. .

CN119284869APending Publication Date: 2025-01-10LIYANG HINA BATTERY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411341963.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing sodium ion batteries are difficult to maintain good cycling performance while increasing their energy density, especially because the low specific capacity value (CB value) leads to uneven sodium deposition and increased side reactions, which affects the stability of the battery.

Method used

The spherical hard carbon covered with Na2Ti6O13 is used as the negative electrode material, and combined with specific positive electrode materials and electrolyte formulations, the conduction uniformity of sodium ions and the injection volume of electrolyte are improved through the matching of the coating layer and electrolyte. Reduce uneven sodium deposition and side reactions.

Benefits of technology

The high energy density and good circulation performance of sodium ion batteries are achieved, which reduces uneven sodium deposition and side reactions, and improves the stability and circulation ability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284869A_ABST
    Figure CN119284869A_ABST
Patent Text Reader

Abstract

The invention relates to a negative electrode material and a high energy density sodium ion battery, the negative electrode material comprises a positive plate, a negative plate, an electrolyte and a diaphragm, the positive electrode material of the positive plate is a layered transition metal oxide with a coating layer on the surface, the negative electrode material of the negative plate is spherical hard carbon with Na2Ti6O13 coated on the surface, the electrolyte is an ether electrolyte, and the diaphragm is a lithium ion battery. And the CB value of the sodium ion battery is 0.4 to 0.8. As the capacity of the battery is determined by the capacity of the positive electrode, the capacity of the negative electrode in the unit area of the sodium ion battery is lower than the capacity of the positive electrode, so that the ratio of the negative electrode in the battery is reduced, the ratio of the positive electrode in the battery is increased, and a sodium deposition layer can be prevented from being formed on the surface of the negative electrode by selecting the specific positive electrode material, negative electrode material and electrolyte. The sodium ion battery prepared by matching the materials has relatively high energy density and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a negative electrode material and a high energy density sodium ion battery. Background Art

[0002] Compared with lithium-ion batteries, sodium-ion batteries have certain cost advantages, but their energy density is relatively low, so the watt-hour cost has not decreased. In order to further reduce the watt-hour cost, the energy density of the battery needs to be increased. The common method to increase capacity density is to use high-capacity positive and negative electrode materials, but the development cycle of high-capacity materials is long and the cost is relatively high, so the effect on reducing the watt-hour cost is relatively small. Using no negative electrode or reducing the battery CB value is a relatively radical improvement method, which has obvious effects but poor cycle performance. Summary of the invention

[0003] In view of the above analysis, the present invention aims to provide a negative electrode material and a high energy density sodium ion battery to solve the problem that the sodium ion battery with low CB value in the prior art cannot meet both high energy density and good cycle performance.

[0004] In the first aspect, the present invention provides a surface-coated Na2Ti6O 13 The method for preparing spherical hard carbon comprises the following steps:

[0005] (1) heating the spherical phenolic resin for a first time to perform pre-carbonization and sintering, crushing, and heating it for a second time to obtain a first intermediate product;

[0006] (2) adding the first intermediate product to the first solution and stirring to mix evenly, adding the second solution, stirring evenly, and drying to obtain a second intermediate product;

[0007] (3) Sintering the second intermediate product to obtain the surface-coated Na2Ti6O 13 Spherical hard carbon.

[0008] Furthermore, in step (1), the first heating rate is 2-5°C / min, the temperature is raised to 500-800°C, and the sintering is carried out at this temperature for 2-4h.

[0009] Furthermore, in step (1), the second heating rate is 5-10°C / min, the temperature is raised to 1000-1400°C, and the sintering is carried out at this temperature for 3-5h.

[0010] Furthermore, in step (2), the mass volume ratio of the first intermediate product to the first solution and the second solution is 10-50 g: 20-25 ml: 7-9 mL.

[0011] In a second aspect, the present invention provides a negative electrode material, wherein the negative electrode material is a surface-coated Na2Ti6O prepared by the above method. 13 Spherical hard carbon.

[0012] In a third aspect, the present invention provides a high energy density sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode material of the positive electrode sheet is a layered transition metal oxide having a coating layer on the surface, and the negative electrode material of the negative electrode sheet is a layered transition metal oxide having a coating layer on the surface prepared by the above method. 13 The spherical hard carbon is an ether electrolyte, and the CB value of the sodium ion battery is 0.4 to 0.8.

[0013] Furthermore, the coating layer is one or more of C, Al2O3, phosphate or sulfate.

[0014] Furthermore, the ether is diethylene glycol dimethyl ether or DME, and the electrolyte also includes NaPF6, NaBF4 and oxalate.

[0015] Furthermore, the molar concentration ratio of NaPF6, NaBF4 and oxalate is 0.85-0.9:0.05-0.2:0.01-0.1.

[0016] Furthermore, 2g / Ah<the electrolyte injection coefficient<3.5g / Ah; and / or, the puncture resistance strength of the diaphragm is>500gf.

[0017] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0018] (1) The surface-coated Na2Ti6O prepared by the present invention 13 Spherical hard carbon is used as the negative electrode material of sodium ion batteries and is used in sodium ion batteries with low CB value. 13 It is a fast ion conductor. When coated on the surface of the material, it can quickly conduct the sodium ions coming from the positive electrode, making the sodium ion concentration more balanced everywhere, further reducing the uneven deposition of sodium and improving the cycle capacity of the battery.

[0019] (2) The CB value (ratio of negative electrode capacity to positive electrode capacity) used in existing battery designs is 1.0 to 1.2, and the negative electrode capacity must be higher than the positive electrode capacity to prevent sodium precipitation. Since the capacity of the battery is determined by the capacity of the positive electrode, the negative electrode capacity per unit area of ​​the sodium ion battery of the present invention is lower than the positive electrode capacity, thereby reducing the proportion of the negative electrode in the battery and increasing the proportion of the positive electrode. In the present invention, by selecting specific positive electrode materials, negative electrode materials and electrolytes, the uniformity of sodium deposition is facilitated, and the sodium ion battery prepared by matching the materials has a higher energy density and cycle performance;

[0020] (3) The positive electrode material of the present invention contains transition metals, which are easily partially dissolved as the positive electrode structure changes. The dissolved metal elements will damage the SEI (solid electrolyte interface) of the negative electrode material, thereby aggravating the side reactions of the negative electrode. Therefore, it is necessary to appropriately coat the positive electrode material to reduce the dissolution of transition metal elements and improve the cycle performance of the battery;

[0021] (4) Surface coating with Na2Ti6O 13 The spherical hard carbon has a uniform shape and can form a relatively uniform reaction everywhere on the surface, which is beneficial to the uniformity of the sodium deposition layer. 13 It is a fast ion conductor. When coated on the surface of the material, it can quickly conduct the sodium ions coming from the positive electrode, making the sodium ion concentration more balanced everywhere and further reducing uneven deposition.

[0022] (5) The reason for setting the injection coefficient is that during the cycle, a small amount of side reactions still occur between the sodium metal precipitated in the later stage and the electrolyte. Therefore, the amount of electrolyte injection cannot be too small. If it is too small, the amount of electrolyte will be insufficient in the later stage of the cycle. However, it cannot be too much either, because the side reactions will produce gas. If there is too much electrolyte, there will be less space for gas in the cylindrical shell, and the cylinder is easy to flip. Therefore, in the present invention, the injection coefficient of the electrolyte is 2g / Ah<3.5g / Ah.

[0023] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0025] Figure 1 The surface-coated Na2Ti6O prepared in Example 1 of the present invention 13 SEM image of spherical hard carbon. DETAILED DESCRIPTION

[0026] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0027] A specific embodiment of the present invention discloses a surface-coated Na2Ti6O 13The method for preparing spherical hard carbon comprises the following steps:

[0028] (1) heating the spherical phenolic resin for a first time to perform pre-carbonization and sintering, crushing, and heating it for a second time to obtain a first intermediate product;

[0029] (2) adding the first intermediate product to the first solution and stirring to mix evenly, adding the second solution, stirring evenly, and drying to obtain a second intermediate product;

[0030] (3) Sintering the second intermediate product to obtain the surface-coated Na2Ti6O 13 Spherical hard carbon.

[0031] The surface coated Na2Ti6O prepared by the present invention 13 Spherical hard carbon is used as the negative electrode material of sodium ion batteries and is used in sodium ion batteries with low CB value. 13 It is a fast ion conductor. When coated on the surface of the material, it can quickly conduct the sodium ions coming from the positive electrode, making the sodium ion concentration everywhere more balanced, further reducing the uneven deposition of sodium and improving the cycle capacity of the battery.

[0032] In a specific embodiment, in step (1), the particle size of the spherical phenolic resin is 2 to 7 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, or 7 μm.

[0033] In a specific embodiment, in step (1), the first heating rate is 2-5°C / min, for example, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min; the temperature is increased to 500-800°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, and sintered for 2-4h, and the sintering time is 2h, 2.5h, 3h, 3.5h, 4h.

[0034] It should be noted that the first heating temperature is within the temperature range for removing volatile substances, and the heat preservation is also for removing volatile substances. The above heating rate ensures that the time is not too long and the volatile substances are removed relatively cleanly.

[0035] In a specific embodiment, in step (1), the second heating rate is 5-10°C / min, for example, 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min, 7°C / min, 7.5°C / min, 8°C / min, 8.5°C / min, 9°C / min, 9.5°C / min, 10°C / min, and the temperature is increased to 1000-1400°C, for example, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, and the temperature is kept at this temperature for 3-5h, for example, 3h, 3.5h, 4h, 4.5h, 5h.

[0036] The second heating treatment is a carbonization process. Excessive carbonization leads to reduced capacity, while insufficient carbonization leads to a large specific surface area and low initial efficiency. Therefore, the present invention selects the above-mentioned heating rate, temperature and insulation time.

[0037] In a specific embodiment, in step (2), the first solution is a mixture of tetrabutyl titanate and ethanol in a volume ratio of 1:20.

[0038] In a specific embodiment, in step (2), the second solution is a mixture of sodium carbonate and ethanol in a mass volume ratio of 1 g:20 mL.

[0039] In a specific embodiment, in step (2), the mass volume ratio of the first intermediate product to the first solution and the second solution is 10-50g:20-25mL:7-9mL, for example, 10g:25mL:7mL, 30g:21mL:8mL, 40g:23mL:9mL, 50g:24mL:8mL.

[0040] In a specific embodiment, in step (3), the sintering temperature is 600-1000°C, for example, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, and the sintering time is 3-6h, for example, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h.

[0041] Another specific embodiment of the present invention is a negative electrode material, wherein the negative electrode material is a surface-coated Na2Ti6O prepared by the above method. 13 Spherical hard carbon.

[0042] Another specific embodiment of the present invention discloses a high energy density sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode material of the positive electrode sheet is a layered transition metal oxide with a coating layer on the surface, and the negative electrode material of the negative electrode sheet is a layered transition metal oxide with a coating layer on the surface. 13The spherical hard carbon is an ether electrolyte, and the CB value of the sodium ion battery is 0.4 to 0.8.

[0043] The CB value (ratio of negative electrode capacity to positive electrode capacity) used in existing battery designs is 1.0 to 1.2, and the negative electrode capacity must be higher than the positive electrode capacity to prevent sodium precipitation. Since the capacity of the battery is determined by the capacity of the positive electrode, the negative electrode capacity per unit area of ​​the sodium ion battery of the present invention is lower than the positive electrode capacity, thereby reducing the proportion of the negative electrode in the battery and increasing the proportion of the positive electrode. In the present invention, by selecting specific positive electrode materials, negative electrode materials and electrolytes, it is helpful to achieve uniformity of sodium deposition, and the sodium ion battery prepared by matching the materials has higher energy density and cycle performance.

[0044] Specifically, the positive electrode material of the present invention contains transition metals, and the transition metal elements are easily partially dissolved as the positive electrode structure changes. The dissolved metal elements will damage the SEI (solid electrolyte interface) of the negative electrode material, thereby aggravating the side reactions of the negative electrode. Therefore, it is necessary to appropriately coat the positive electrode material to reduce the dissolution of transition metal elements and improve the cycle performance of the battery.

[0045] Since the battery of the present invention has a low CB value, it is inevitable to form a sodium deposition layer, so it is necessary to control the formation of a uniform and compact sodium deposition layer as much as possible. This is because an uneven sodium deposition layer will form dendrites, which will penetrate the diaphragm and cause a direct short circuit in the battery, and will also increase the side reaction between the sodium deposition layer and the electrolyte, and basically have no circulation capacity. Spherical hard carbon, in contrast, has a uniform shape and can form a relatively uniform reaction everywhere on the surface, so it is beneficial to the uniformity of the sodium deposition layer. Na2Ti6O 13 It is a fast ion conductor. When coated on the surface of the material, it can quickly conduct the sodium ions coming from the positive electrode, making the sodium ion concentration everywhere more balanced and further reducing uneven deposition.

[0046] Since the negative electrode capacity per unit area is smaller than the positive electrode capacity, a sodium deposit layer will form on the negative electrode surface. When the electrolyte is not properly matched, the sodium deposit layer is prone to react with the electrolyte continuously, deteriorating the battery performance. Among them, ether electrolytes are conducive to forming a uniform and smooth sodium deposit layer and are not prone to side reactions with the sodium deposit layer, which is beneficial to the stability of the entire system.

[0047] In a specific implementation method, the coating layer is one or more of C, Al2O3, phosphate or sulfate.

[0048] Specifically, the phosphate is one or more of sodium iron phosphate, sodium vanadium phosphate, sodium iron pyrophosphate or sodium titanium phosphate, etc., the sulfate is sodium iron sulfate, and the layered transition metal oxides with coating layers described in the present invention are all prepared by existing methods or commercially available raw materials, for example, the layered transition metal oxides are coated with reference to the method of patent CN117936748A. C, Al2O3, phosphate or sulfate can increase the electronic conductivity or ionic conductivity of the positive electrode material, which is beneficial to the battery cycle.

[0049] In a specific embodiment, the ether is diethylene glycol dimethyl ether or DME (dimethyl ether).

[0050] In a specific embodiment, the electrolyte further comprises NaPF6 and NaBF4. NaPF6 and NaBF4 can assist in forming a relatively stable surface SEI protective film and can also reduce the occurrence of side reactions.

[0051] In a specific embodiment, the electrolyte further includes oxalate, and the oxalate is one or more of sodium dioxalate difluorophosphate, LiBODFP (lithium difluorodioxalate phosphate), sodium bis(oxalate)borate, and sodium tri(oxalate)phosphate. This is because the above substances can cooperate with the metal elements dissolved from the positive electrode to prevent the transition metal elements from diffusing to the negative electrode to destroy the negative electrode SEI film.

[0052] In a preferred embodiment, the molar concentration ratio (mol / L) of NaPF6, NaBF4 and oxalate is 0.85-0.9:0.05-0.2:0.01-0.1, for example, 0.85:0.2:0.01, 0.86:0.15:0.03, 0.88:0.1:0.05, 0.9:0.05:1.

[0053] In a specific embodiment, the electrolyte injection coefficient is 2g / Ah<3.5g / Ah, for example, 2.1g / Ah, 2.3g / Ah, 2.5g / Ah, 2.7g / Ah, 2.9g / Ah, 3.1g / Ah, 3.3g / Ah, 3.4g / Ah.

[0054] It should be noted that the filling coefficient is set mainly because during the circulation process, a small number of side reactions still occur between the sodium metal precipitated in the later stage and the electrolyte. Therefore, the amount of electrolyte injection cannot be too small. If it is too small, the amount of electrolyte will be insufficient in the later stage of the cycle. However, it cannot be too much either, because the side reactions will produce gas. If there is too much electrolyte, there will be less space left for gas in the cylindrical shell, and the cylinder will easily flip over.

[0055] In a specific embodiment, the puncture resistance of the diaphragm is greater than 500 gf.

[0056] It should be noted that a higher puncture resistance can prevent the presence of slightly uneven deposition in some areas, thereby preventing sodium metal from puncturing the separator and preventing short circuits that may lead to battery failure.

[0057] In the present invention, the negative electrode plate is prepared using an oil system, NMP (N-methyl-2-pyrrolidone) is selected as a dispersing solvent, PVDF (polyvinylidene fluoride) is selected as a binder, and CNT (carbon nanotube) is added as a conductive agent. In the present invention, the moisture content of the negative electrode plate is controlled to be less than 150ppm, and the moisture content of the positive electrode plate is controlled to be less than 150ppm.

[0058] This is because spherical hard carbon has a porous structure, so it is easy to absorb water and difficult to dry out. The presence of water will intensify the side reaction between the sodium deposit layer and the electrolyte, which needs to be avoided as much as possible. Therefore, an oil system is used to reduce the contact between the negative electrode material and water, so that the moisture content of the electrode is controlled at a lower level, and the moisture content of the positive electrode should also be controlled at a lower level.

[0059] The high energy density sodium ion battery of the present invention has a battery capacity of 4534-5835 mAh / g, a battery energy density of 173.3-217.9 Wh / kg, and a capacity retention rate of 81.3-96.2% after 100 cls of cycling at room temperature and 0.5C.

[0060] Another specific embodiment of the present invention discloses a method for preparing a high energy density sodium ion battery, comprising the following steps:

[0061] (a) Preparation of positive electrode sheet: positive electrode material, binder, conductive agent and solvent are mixed, coated on aluminum foil, compacted and cut to obtain positive electrode sheet;

[0062] (b) Preparation of negative electrode sheet: negative electrode material, binder, conductive agent and solvent are mixed, coated on aluminum foil, compacted and cut to obtain negative electrode sheet;

[0063] (c) Preparation of battery: The positive electrode sheet, negative electrode sheet and separator are placed in a shell, and an electrolyte is added, the shell is sealed and activated to obtain the sodium ion battery.

[0064] The technical solution of the present invention is further explained below in conjunction with specific embodiments. It should be noted that all raw materials in the present invention are commercially available raw materials or raw materials prepared according to existing methods, and the preparation method of the Al2O3-coated NFM424 layered oxide positive electrode material in the following embodiments is prepared by referring to patent CN117936748A.

[0065] The manufacturer of the 12+2+2 diaphragm is the SW16 series of Shenzhen Xingyuan Material Technology Co., Ltd., and the manufacturer of the 12μm base film is the E10 series of Shenzhen Xuran Electronics Co., Ltd. The above models are used as examples for explanation in the present invention, but the protection scope of the present invention is not limited to this.

[0066] Example 1

[0067] A high energy density sodium ion battery of this embodiment, the specific preparation method is as follows:

[0068] (a) Preparation of positive electrode sheet: Al2O3-coated NFM424 layered oxide positive electrode material was mixed with binder PVDF, conductive agent SP, CNT, and oxalic acid in a mass ratio of 95.5%:1.7%:2.0%:0.5%:0.3% using NMP as solvent. After being mixed evenly, the mixture was plated with a single-sided surface density of 16.7 mg / cm 2 The positive electrode sheet is formed by coating on aluminum foil, and the positive electrode sheet is rolled to a compaction density of 3.25 g / cc. The rolled positive electrode sheet is cut into strips to obtain the required positive electrode sheet.

[0069] (b) Preparation of negative electrode: The surface is coated with Na2Ti6O 13 The spherical hard carbon material, the binder PVDF, the conductive agent SP and the CNT were mixed in a mass ratio of 94.5%:3%:2%:0.5% with NMP as the solvent. After being mixed evenly, the single-sided surface density was 6.5 mg / cm 2 The negative electrode sheet is formed by coating on aluminum foil, and the negative electrode sheet is rolled to a compaction density of 0.95 g / cc. The rolled negative electrode sheet is cut into strips to obtain the required negative electrode sheet.

[0070] Among them, the surface is coated with Na2Ti6O 13 The spherical hard carbon material is prepared by the following method:

[0071] (1) heating a spherical phenolic resin having a particle size of 2-7 μm to 600° C. at a heating rate of 5° C. / min for the first time, and pre-carbonizing and sintering the spherical phenolic resin for 12 hours at a heating rate of 5° C. / min, crushing the spherical phenolic resin, and heating the spherical phenolic resin for the second time to 1200° C. at a heating rate of 5° C. / min, and pre-carbonizing and sintering the spherical phenolic resin for 5 hours to obtain a first intermediate product;

[0072] (2) adding the first intermediate product to the first solution and stirring to mix evenly, wherein the first solution is a mixture of tetrabutyl titanate and ethanol at a volume ratio of 1:20, and the mass volume ratio of the first intermediate product to the first solution is 20 g:24 mL, adding the second solution and stirring evenly, wherein the second solution is a mixture of sodium carbonate and ethanol at a mass volume ratio of 1 g:20 mL, and the mass volume ratio of the first intermediate product to the second solution is 20 g:9 mL, and drying to obtain the second intermediate product;

[0073] (3) Sintering the second intermediate product at 800°C for 5 hours to obtain the surface-coated Na2Ti6O 13 Spherical hard carbon, electron microscope image Figure 1 shown.

[0074] (c) Production of battery: The positive and negative electrode sheets prepared above are welded to the 12+2+2 separator with a puncture resistance strength of 600gf, and the electrode ears are welded and wound into the shell. The opened battery core is baked to obtain a moisture content of less than 150ppm for the positive electrode sheet and less than 150ppm for the negative electrode sheet. The battery core is injected with electrolyte, and the electrolyte is prepared by mixing NaPF6, NaBF4, and LiBODFP in a molar concentration ratio of 0.88:0.1:0.02 with diethylene glycol dimethyl ether as solvent, and then the sealing process is performed, and the battery after injection (injection coefficient is 2.8g / Ah) is activated to obtain the battery.

[0075] The CB value of the sodium ion battery is 0.74.

[0076] Example 1-1

[0077] The preparation method of the high energy density sodium ion battery in this embodiment is the same as that in embodiment 1, except that the surface is coated with Na2Ti6O 13 The spherical hard carbon material is prepared by the following method:

[0078] (1) heating a spherical phenolic resin having a particle size of 2-7 μm to 500° C. at a heating rate of 25° C. / min for the first time, and pre-carbonizing and sintering the spherical phenolic resin for 4 hours at a heating rate of 25° C. / min, crushing the spherical phenolic resin, and heating the spherical phenolic resin for the second time to 1400° C. at a heating rate of 10° C. / min, and pre-carbonizing and sintering the spherical phenolic resin for 4 hours to obtain a first intermediate product;

[0079] (2) adding the first intermediate product to the first solution and stirring to mix evenly, wherein the first solution is a mixture of tetrabutyl titanate and ethanol at a volume ratio of 1:20, and the mass volume ratio of the first intermediate product to the first solution is 40 g:20 mL, adding the second solution and stirring evenly, wherein the second solution is a mixture of sodium carbonate and ethanol at a mass volume ratio of 1 g:20 mL, and the mass volume ratio of the first intermediate product to the second solution is 40 g:7 mL, and drying to obtain the second intermediate product;

[0080] (3) Sintering the second intermediate product at 600°C for 6 hours to obtain the surface-coated Na2Ti6O 13 Spherical hard carbon.

[0081] Example 1-2

[0082] The preparation method of the high energy density sodium ion battery in this embodiment is the same as that in embodiment 1, except that the surface is coated with Na2Ti6O 13 The spherical hard carbon material is prepared by the following method:

[0083] (1) heating a spherical phenolic resin having a particle size of 2-7 μm to 800° C. at a heating rate of 3° C. / min for the first time, and pre-carbonizing and sintering the spherical phenolic resin for 2 h at a heating rate of 3° C. / min, crushing the spherical phenolic resin, and heating the spherical phenolic resin for the second time to 1000° C. at a heating rate of 7° C. / min, and pre-carbonizing and sintering the spherical phenolic resin for 3 h to obtain a first intermediate product;

[0084] (2) adding the first intermediate product to the first solution and stirring to mix evenly, wherein the first solution is a mixture of tetrabutyl titanate and ethanol at a volume ratio of 1:20, and the mass volume ratio of the first intermediate product to the first solution is 50 g:20 mL, adding the second solution and stirring evenly, wherein the second solution is a mixture of sodium carbonate and ethanol at a mass volume ratio of 1 g:20 mL, and the mass volume ratio of the first intermediate product to the second solution is 50 g:7 mL, and drying to obtain the second intermediate product;

[0085] (3) Sintering the second intermediate product at 1000°C for 3 hours to obtain the surface-coated Na2Ti6O 13 Spherical hard carbon.

[0086] Example 2

[0087] The preparation method of a high energy density sodium ion battery in this embodiment is the same as that in embodiment 1, except that: in the preparation of the positive electrode sheet, a single-sided surface density of 20.5 mg / cm 2 Coated on aluminum foil to form the positive electrode sheet, and the negative electrode sheet was prepared with a single-sided surface density of 5 mg / cm 2The negative electrode is formed by coating on aluminum foil. The CB value of the sodium ion battery is 0.46.

[0088] Example 3

[0089] The preparation method of a high energy density sodium ion battery in this embodiment is the same as that in embodiment 1, except that: the positive electrode material is a NFM424 layered oxide positive electrode material coated with sodium iron sulfate, and the single-sided surface density of 16.7 mg / cm 2 The positive electrode is formed by coating on aluminum foil, and the CB value of the sodium ion battery is 0.74.

[0090] Among them, the sodium iron sulfate-coated NFM424 layered oxide positive electrode material is prepared by the following method: ball-milling sodium iron phosphate to a particle size of 1-3 μm, blending NFM424 layered oxide and sodium sulfate in a ratio of 10:0.5, and ball-milling for 1-2 hours to obtain the sodium iron sulfate-coated NFM424 layered oxide positive electrode material.

[0091] Example 4

[0092] The preparation method of a high energy density sodium ion battery in this embodiment is the same as that in Example 1, except that: the preparation of the battery: the electrolyte is prepared by mixing diethylene glycol dimethyl ether as a solvent, NaPF6, NaBF4, and LiBODFP in a molar concentration ratio of 0.88:0.1:0.05.

[0093] Example 5

[0094] The preparation method of a high energy density sodium ion battery in this embodiment is the same as that in Example 1, except that: the preparation of the battery: the electrolyte uses diethylene glycol dimethyl ether as a solvent, and NaPF6, NaBF4, and LiBODFP are mixed in a molar concentration ratio of 0.88:0.1:0.02, and the injection coefficient is 2.1 g / Ah.

[0095] Example 6

[0096] The preparation method of a high energy density sodium ion battery in this embodiment is the same as that in embodiment 1, except that: in the preparation of the positive electrode sheet, a single-sided surface density of 20.5 mg / cm 2 Coated on aluminum foil to form the positive electrode sheet, and the negative electrode sheet was prepared with a single-sided surface density of 6.5 mg / cm 2 The negative electrode is formed by coating on aluminum foil, and the CB value of the sodium ion battery is 0.6.

[0097] Comparative Example 1

[0098] The preparation method of the sodium ion battery in this comparative example is the same as that in Example 1, except that the positive electrode sheet is prepared with a single-sided surface density of 15 mg / cm2 Coated on aluminum foil to form the positive electrode sheet, and the negative electrode sheet was prepared with a single-sided surface density of 8.5 mg / cm 2 The negative electrode is formed by coating on aluminum foil, and the CB value of the sodium ion battery is 1.11.

[0099] Comparative Example 2

[0100] The preparation method of the sodium ion battery of this comparative example is the same as that of Example 1, except that the positive electrode material is NFM424 layered oxide positive electrode material.

[0101] Comparative Example 3

[0102] The preparation method of the sodium ion battery of this comparative example is the same as that of Example 1, except that the 12+2+2 separator is replaced by a 12 μm base film (commercially available), and the puncture resistance of the base film is 300 gf.

[0103] Comparative Example 4

[0104] The preparation method of the sodium ion battery in this comparative example is the same as that in Example 1, except that the negative electrode is prepared by coating the surface with Na2Ti6O 13 The spherical hard carbon material is mixed with dispersant CMC, adhesive SBR and conductive agent SP in a ratio of 94.7%: 2%: 2.8%: 0.5% with water as solvent. After being mixed evenly, the single surface density is 6.5mg / cm 2 Coating on aluminum foil to form a negative electrode sheet, and rolling the negative electrode sheet to a compaction density of 0.95 g / cc, and cutting the rolled negative electrode sheet into strips to obtain the required negative electrode sheet;

[0105] During battery manufacturing, the moisture content of the negative electrode is 217ppm.

[0106] Comparative Example 5

[0107] The preparation method of the sodium ion battery of this comparative example is the same as that of Example 1, except that the injection coefficient is 1.9 g / Ah.

[0108] Comparative Example 6

[0109] The preparation method of the sodium ion battery in this comparative example is the same as that in Example 1, except that the negative electrode material is spherical hard carbon, and the spherical hard carbon is coated with Na2Ti6O 13 The preparation method of the spherical hard carbon material is different in that only step one (1) is performed to heat the spherical phenolic resin for the first time to perform pre-carbonization and sintering, crush it, and heat it for the second time to obtain the first intermediate product, namely the spherical hard carbon.

[0110] Comparative Example 7

[0111] The preparation method of the sodium ion battery of this comparative example is the same as that of Example 1, except that the molar concentration ratio of NaPF6, NaBF4 and LiBODFP in the electrolyte is 0.65:0.2:0.15.

[0112] Test Example 1

[0113] The electrical properties of the sodium ion batteries prepared in Examples 1-6 and Comparative Examples 1-7 were tested respectively, and the results are shown in Table 1. Among them, the test method for the retention rate of 100 cls cycle at room temperature and 0.5C is as follows:

[0114] 1. The battery is discharged at 0.5C constant current to 2V Rest for 10min;

[0115] 2. 0.5C constant current and constant voltage charge to 4.25V Rest10min;

[0116] 3. 0.5C constant current discharge to 2V Rest10min;

[0117] 4. Cycle steps 2-3 for 100 cls, record the discharge capacity of the 3rd cycle as C3, and record the discharge capacity of the 100th cycle as C100 (retention rate of 100 cls cycle at room temperature 0.5C = C100 / C3).

[0118] Table 1

[0119]

[0120]

[0121] Compared with Example 1, Comparative Example 1 is not within the CB value of the present invention, and the battery energy density of the obtained battery is significantly reduced. Compared with Example 1, Comparative Example 2 has a significantly reduced cycle performance when the normal material is not coated with Al2O3. Compared with Example 1, Comparative Example 3 has a reduced cycle performance when the puncture resistance of the base film is low. Compared with Example 1, Comparative Example 4 has a reduced cycle performance when the moisture content of the negative electrode sheet is too high. Compared with Example 1, Comparative Example 5 has a liquid injection coefficient that is not within the range defined by the present invention, and the cycle performance is significantly reduced. Compared with Example 1, Comparative Example 6 uses ordinary spherical hard carbon, and the cycle performance of the battery is significantly reduced. Compared with Example 1, Comparative Example 7 has components in the electrolyte that are not within the range defined by the present invention, and the cycle performance of the battery is poor.

[0122] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A surface coated Na2Ti6O 13 A method for preparing spherical hard carbon, characterized in that: The steps include: (1) heating the spherical phenolic resin for a first time to perform pre-carbonization and sintering, crushing, and heating it for a second time to obtain a first intermediate product; (2) adding the first intermediate product to the first solution and stirring to mix evenly, adding the second solution, stirring evenly, and drying to obtain a second intermediate product; (3) Sintering the second intermediate product to obtain the surface-coated Na2Ti6O 13 Spherical hard carbon.

2. A surface-coated Na2Ti6O according to claim 1 13 A method for preparing spherical hard carbon, characterized in that: In step (1), the first heating rate is 2-5°C / min, the temperature is raised to 500-800°C, and the temperature is kept and sintered for 2-4h.

3. A surface-coated Na2Ti6O according to claim 1 13 A method for preparing spherical hard carbon, characterized in that: In step (1), the second heating rate is 5-10°C / min, the temperature is raised to 1000-1400°C, and the temperature is kept and sintered for 3-5 hours.

4. The surface-coated Na2Ti6O according to claim 1 13 A method for preparing spherical hard carbon, characterized in that: In step (2), the mass volume ratio of the first intermediate product to the first solution and the second solution is 10-50 g: 20-25 ml: 7-9 mL.

5. A negative electrode material, characterized in that: The negative electrode material is a surface-coated Na2Ti6O prepared by the method of any one of claims 1 to 4. 13 Spherical hard carbon.

6. A high energy density sodium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode material of the positive electrode sheet is a layered transition metal oxide with a coating layer on the surface, and the negative electrode material of the negative electrode sheet is a surface-coated Na2Ti6O 13 The spherical hard carbon is an ether electrolyte, and the CB value of the sodium ion battery is 0.4 to 0.

8.

7. A high energy density sodium ion battery according to claim 6, characterized in that: The coating layer is one or more of C, Al2O3, phosphate or sulfate.

8. A high energy density sodium ion battery according to claim 6, characterized in that: The ether is diethylene glycol dimethyl ether or DME, and the electrolyte also includes NaPF6, NaBF4 and oxalate.

9. A high energy density sodium ion battery according to claim 8, characterized in that: The molar concentration ratio of NaPF6, NaBF4 and oxalate is 0.85-0.9:0.05-0.2:0.01-0.

1.

10. A high energy density sodium ion battery according to any one of claims 6 to 9, characterized in that: 2g / Ah<the electrolyte injection coefficient<3.5g / Ah; and / or, the puncture resistance strength of the diaphragm is>500gf.

Citation Information

Cited By

  • Closed valve control type power battery with high energy and high charging efficiency

    CN120073090A